4x+x+12-4+2x=

Simple and best practice solution for 4x+x+12-4+2x= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x+x+12-4+2x= equation:


Simplifying
4x + x + 12 + -4 + 2x = 0

Reorder the terms:
12 + -4 + 4x + x + 2x = 0

Combine like terms: 12 + -4 = 8
8 + 4x + x + 2x = 0

Combine like terms: 4x + x = 5x
8 + 5x + 2x = 0

Combine like terms: 5x + 2x = 7x
8 + 7x = 0

Solving
8 + 7x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + 7x = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 7x = 0 + -8
7x = 0 + -8

Combine like terms: 0 + -8 = -8
7x = -8

Divide each side by '7'.
x = -1.142857143

Simplifying
x = -1.142857143

See similar equations:

| 315=5x(9) | | 8z+7z=45 | | 6x-(x+2)=3x+11-x | | y-x=100 | | -7(w-2)=4w-8 | | 8z=6z-1 | | 4p-4=2p+44 | | x=0.20x+10 | | 63=-16t^2+64t+3 | | 3-5n-3n=35-72 | | x=0.20x | | -4(m-8)=2m-4 | | 4(6+q)=64 | | 6x-x+2=3x+11-x | | (4x+9x)*(8y+2x)=92 | | -10(-y-9)= | | 7-3x+1=4x+1 | | 142=40(5)+6 | | 142=40(x)+6 | | -(-m+7)= | | -35=5/7u | | 6(-1-6z)=-6 | | 16/5=-8v | | 8x^3+27x^2+54x+27=0 | | 25=-5/3v | | 54+2x=10x-5 | | 5(-3r+9)= | | 10x+12y-2by= | | 4(y-4)+8y=8 | | f(-2)=-3x^2-2x+3 | | 4v/5=8 | | 3x=44x+5 |

Equations solver categories